PENGARUH PENAMBAHAN AIR PERASAN JERUK NIPIS (Citrus aurantiifolia) DALAM AIR MINUM SEBAGAI ACIDIFIER TERHADAP PROFIL LEMAK DARAH AYAM BROILER (The Effect of Citrus aurantifolia Juice Inclusion in Drinking Water as an Acidifier on the Blood Fat Profile of Broilers) - F. Octavia; H. I. Wahyuni (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2018)
The aimed of this study is to determine the effect of jeruk nipis juice (Citrus aurantifolia) as an acidifier against cholesterol, LDL, HDL and triglyceride in blood of broiler. The material that used was 90 DOC (day old chick) with an average weight of 38 ± 0.1 gram. The treatment consisted of T0 (water without the addition of Citrus aurantifolia juice), T1 (water added with 0.5% Citrus aurantifolia juice), and T2 (water added with 1% Citrus aurantifolia juice). This study used the completely randomized design (CRD) consisting of 3 treatments with 6 replications, there were 18 units and each replication unit containing 5 broiler chickens. The Measures parameter are blood fat profiles consisting of cholesterol, LDL, HDL, and triglyceride levels. The results showed that the addition of jeruk nipis juice treatment did not give a significant effect on cholesterol, HDL, LDL, and triglyceride blood of broiler chickens. The conclusion of this study is the addition of jeruk nipis juice (Citrus aurantifolia) that added in drinking water is still maintaining the stability of blood lipid profile that seen from cholesterol, LDL, HDL and triglyceride blood of broiler chickens in a normal range.